Medical student experiences of applying into emergency medicine during the COVID‐19 pandemic: A multi‐institutional survey of emergency medicine–bound medical students. Issue 2 (22nd April 2021) - Jauregui, Joshua; Kessler, Ross; Villalón, Nicholas; House, Joseph; Cole, Michael; Kman, Nicholas; Shandro, Jamie
Abstract: Background: The COVID‐19 pandemic added new and great uncertainty to the typical approach to applying into emergency medicine (EM) for medical students. There are little data on students' lived experience of applying during this time period. We performed a multi‐institutional survey of EM‐bound students' experiences with preparing to apply into EM during the pandemic. Methods: This was a cross‐sectional survey design study of fourth‐year students preparing to apply into EM during the 2020–2021 academic year. All self‐identified EM‐bound students at four participating institutions were recruited by email in June 2020 to participate in a 13‐item, 5‐point Likert‐scale survey. Univariate descriptive statistics, response rate, and nonresponse bias were calculated. Results: Sixty‐seven of 125 eligible students responded for an overall response rate of 53.6%. Nonresponse bias for specific survey items ranged from 0.01 to 0.12. Students rated the importance of securing an EM rotation at their home institution the highest of any item (mean ± SD = 4.81 ± 0.68). Students indicated higher satisfaction with advice from their department of EM (mean ± SD = 4.28 ± 0.75) than from their school of medicine (mean ± SD = 3.52 ± 0.89). Students indicated higher confidence in their home EM rotations' ability to assure adequate personal protective equipment (PPE; mean ± SD = 3.91 ± 0.83) than an away rotation (mean ± SD = 2.82, 1.09). Students reported feeling between moderately and quite stressed about applying into EM this year (mean ± SD = 3.49 ± 1.01), but reported the financial stress the lowest of any item (mean ± SD = 1.46 ± 0.84). Students rated it highly important that away rotations prioritize students from institutions without an EM residency (mean ± SD = 4.51 ± 0.93). Conclusion: Medical students applying into EM during the COVID‐19 pandemic felt confident in their EM advisors' recommendations and their home institution's PPE provision. Students with EM residency programs at their schools recognized the importance of away rotations being prioritized for students from schools without EM residency programs. Strong EM advising is important to students.